Islamic Fintech Business Model and Regulation in Indonesia - Surbakti Mhd Handika; Mohamad Soleh Nurzaman (Al Tijarah, 2024)
The growth of the sharia financial technology (fintech) industry in Indonesia presents a joint task with stakeholders, namely increasing literacy in order to create a conducive ecosystem for the development and sustainability of sharia fintech. This study aims to systematically explain the various Islamic fintech business models in Indonesia and transaction schemes to the regulations and regulators that regulate and supervise them. This study uses a qualitative approach and descriptive analysis (qualitative descriptive analysis). This preliminary research found that there are four sharia fintech business models operating in Indonesia, namely: fintech payment, peer to peer lending, securities crowdfunding and digital financial innovation. The regulators that carry out regulation and supervision are Bank Indonesia (Ministry of Payment System Policy), Financial Services Authority (Directorate of Fintech Regulation, Licensing, and Supervision, Department of Capital Markets and Digital Finance and Innovation Group) and the Indonesian Ulema Council (National Sharia Council). The author suggests that further researchers can explore the study of each of these sharia fintech clusters, both in terms of regulation, consumer behavior, business model development and so on.